E. Laclau and Bergson: The Comic Experience as a Mobilising Element in the Construction of a People - Gómez Villar, Antonio (Res Publica. Revista de Historia de las Ideas Políticas, 2023)
Taking H. Bergson’s reflections on laughter as my starting point, I speculate about the specific elements of the humour in E. Laclau’s populist logic; about the emotional links that are forged between the leader and the people through comic strategies; and about the extent to which humour may serve as a mobilising element for the construction of a people. Rather than attributes of an independent political agency, I reflect instead on humour as an attribute of iconographic representation in the sense conferred on it by E. Laclau. While for H. Bergson laughter fulfils a corrective social function, I invite reflection on the comic experience as an intensifying function in the construction of collective identities.
Keywords: Laclau; Bergson; populism; humour; the leader; laughter